Disturbance of thalamic metabolism and its association with regional neural dysfunction and cognitive impairment in minimal hepatic encephalopathy. Issue 131 (October 2020) - Chen, Li-Hong; Shi, Jia-Yan; Zou, Tian-Xiu; Zhang, Ling; Gou, Yaoping; Lin, Yanqin; Chen, Hua-Jun
Highlights: Thalamic Glx levels increase and Cho/mI level decrease in MHE. Thalamic metabolism disorder progresses with disease development. Altered thalamic metabolism is correlate with cognitive deficit in cirrhosis. Altered intrinsic thalamic activity is associated with metabolism disorder in MHE. Thalamic metabolite measurements may be useful for MHE diagnosis. Abstract: Purpose: To conduct the first investigation on thalamic metabolic alterations in minimal hepatic encephalopathy (MHE) and elucidate their association with intrinsic neural activity change and cognitive dysfunction. Methods: Thirty-eight cirrhotic patients [18 with MHE, 20 without MHE (NHE)] and 21 healthy controls (HC) were included, all of whom underwent 1 H-magnetic resonance spectroscopy, resting-state functional magnetic resonance imaging (fMRI), as well as cognitive assessment based on the Psychometric Hepatic Encephalopathy Score (PHES). Metabolite ratios in the thalamus were measured, including N-acetyl aspartate (NAA)/creatine (Cr), glutamate plus glutamine (Glx)/Cr, choline (Cho)/Cr, and myo-inositol (mI)/Cr. Intrinsic neural activity was evaluated based on frequency-specific amplitude of low-frequency fluctuations (ALFF) using fMRI signals. Results: MHE patients showed an increase in Glx/Cr and a decrease in Cho/Cr and mI/Cr, compared with HC. These changes were aggravated from NHE to MHE. Cho/Cr and mI/Cr were positively correlated with regional ALFF derived from the frequency-specific band (0.01–0.027 Hz) and PHES. Receiver operating characteristic curve analysis showed that Cho/Cr and mI/Cr measurements exhibited moderate discrimination ability between NHE and MHE. Conclusion: Our findings provide evidence that MHE is associated with disturbed metabolism in the thalamus, which may contribute to the altered neural activity and underlie the mechanisms of cognitive impairments. MRS measurements in the thalamus could serve as the potential biomarker for diagnosing MHE among cirrhotic patients.